2018
DOI: 10.1007/s10862-018-9655-9
|View full text |Cite
|
Sign up to set email alerts
|

Unique and Interactive Associations of Callous-Unemotional Traits, Impulsivity and Grandiosity with Child and Adolescent Conduct Disorder Symptoms

Abstract: The construct of psychopathy remains underrepresented in the clinical diagnosis of Conduct Disorder (CD) as the Diagnostic and Statistical Manual of Mental Disorders 5 th edition (DSM-5) only addresses one out of the three dimensions of child psychopathy, Callous Unemotional (CU) traits. This study tests if and to what extent there are unique and interactive associations of CU traits, impulsivity and grandiosity with child and adolescent CD symptoms. Data were collected from two separate community samples of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 44 publications
6
33
0
1
Order By: Relevance
“…More recently, Horan et al (2015) found that factorial invariance and patterns of association of psychopathic traits with external criteria were mostly similar in boys and girls in a community sample of Hispanic and Black adolescents. Finally, studies in this Special Issue were conducted with culturally and ethnically diverse youth from Sweden (Frogner et al 2018), the island of Cyprus (Andershed et al this issue;Fanti et al 2018), and Italy (Somma et al 2018), revealing remarkable consistency among these studies and relative to the current literature based substantially on North American samples. Beyond these important endeavors, the field needs evidence on how familial and sociocultural factors contextualize youth psychopathic traits.…”
Section: Studies Of This Special Sectionmentioning
confidence: 84%
See 2 more Smart Citations
“…More recently, Horan et al (2015) found that factorial invariance and patterns of association of psychopathic traits with external criteria were mostly similar in boys and girls in a community sample of Hispanic and Black adolescents. Finally, studies in this Special Issue were conducted with culturally and ethnically diverse youth from Sweden (Frogner et al 2018), the island of Cyprus (Andershed et al this issue;Fanti et al 2018), and Italy (Somma et al 2018), revealing remarkable consistency among these studies and relative to the current literature based substantially on North American samples. Beyond these important endeavors, the field needs evidence on how familial and sociocultural factors contextualize youth psychopathic traits.…”
Section: Studies Of This Special Sectionmentioning
confidence: 84%
“…Colins et al (2018) intensively ascertained, with separate maternal and paternal ratings, nearly 700 preadolescent boys and girls; the use of all psychopathy dimensions improved predictions of escalating and stable CP relative to CU traits only. Similarly, employing a large sample of children (N = 1599, mean age = 9.5 years), Fanti et al (2018) found improved predictions of CD when impulsivity, grandiosity, and CU traits were simultaneously elevated; however, perhaps more importantly, these predictions were clinically significant given that all three psychopathic trait dimensions predicted an established threshold for clinically severe CD. Finally, a central tenet of developmental psychopathology is that development is characterized by continuity and discontinuity, including non-linear effects.…”
Section: Studies Of This Special Sectionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to occasional aggressive acts, bullying incidents (both online and offline) have been associated with specific personality traits (e.g., Leistico et al 2008). Researchers have frequently referred to psychopathic traits 1 (e.g., Fanti and Kimonis 2012;Fanti et al 2018;Kokkinos et al 2014), which evidently are prevalent among both cyber (e.g., Antoniadou and Kokkinos 2013;Antoniadou et al 2016a), and traditional forms of bullying (Fanti and Kimonis 2013;Sutton and Keogh 2000). Psychopathic traits are not perceived as a unidimensional construct and most studies have focused on the affective dimension (callous-unemotional traits), since lack of concern for others' feelings is highly predictive of both TB (e.g., Fanti and Kimonis 2012) and CB (e.g., Antoniadou et al 2016a).…”
Section: Psychopathic Traitsmentioning
confidence: 99%
“…Embora contribuições individuais das subdimensões psicopáticas sejam amplamente exploradas, pesquisadores vêm ressaltando especificamente o poder diferencial das EPSL, sobretudo na população infanto-juvenil (Fanti et al, 2018). Com efeito, o termo psicopatia, quando utilizado indiscriminadamente, carrega um forte estigma.…”
Section: Considerações Finaisunclassified